Nonisotopic oligomeric probes for the human enteroviruses. - Rotbart, H A (1988)
Oligonucleotide probes were prepared from highly conserved regions of human enteroviral genomes. These reagents were labeled with either 32P or alkaline phosphatase and were successfully used in blot assays to detect a wide variety of human enteroviruses, proving the potential utility of oligomeric sequences as pan-enteroviral probes. The availability of nonisotopic probes will ultimately make a hybridization assay for enteroviruses easier, shorter, and more adaptable for routine diagnostic laboratories.